Risk of tuberculosis among household contacts in Salvador, Bahia - Lemos,Antonio Carlos (2004)
Tuberculosis is one of the most important infectious diseases in the world. Only 68% of the estimated new tuberculosis (TB) cases in Brazil are diagnosed. Our aim was to determine the risk of infection among household contacts. Study design. Cohort of tuberculin-negative household contacts followed for 12 Months. Methods. Household contacts of randomly selected index acid-fast bacilli (AFB)-positive TB cases were evaluated through clinical examination, thorax X-ray, tuberculin, AFB smear and culture. Contacts with a negative response to the tuberculin test (less than 10 mm diameter) were retested after 90 days. Tuberculin reversal (used as a parameter of infection risk) was defined as an increase of at least 10 mm from the last measurement. Results. 269 household contacts were followed. The prevalence of disease in this population was 3.7%. The prevalence of infection after the 12-month follow-up period was 63.9%. The risk of infection was 31.1% within 120 ± 48 days. Conclusion. Household contacts of AFB positive tuberculosis patients have a very high prevalence and risk of tuberculosis infection. TB preventive or therapeutic measures directed towards this group should be implemented in Brazil.